A forest ethic and multivalue forest management: the integrity of forests and of foresters are bound together - Coufal, James E., author; Rolston, Holmes, 1932-2025, author; Society of American Foresters, publisher (Colorado State University. Libraries, 1991)
The Society of American Foresters (SAF) has long had an ethic of using forests to benefit society. Now many foresters, prompted by Aldo Leopold and his land ethic, are wondering if SAF does not need a forest ethic, respecting the integrity of natural systems, to complement its ethic for society. Forests are communities as well as commodities. Forest management ought to expand from an ethical of multiple use to one of protecting multiple values found in forests.
James Coufal, co-author, is in the College of Environmental Science and Forestry, State University of New York, Syracuse, and is former president of SAF.
Keywords: ethical aspects; forest management; environmental ethics; forests and forestry; moral aspects